Overseeing Brands and Client Interaction In Virtual Brand Communities - Zainul Wasik; Lia Febria lina (Journal of Managerial Sciences and Studies, 2025)
The creation and significance of virtual brand communities (VBCs) are of great interest to scholars and practitioners alike, given the enormous shifts in the marketplace driven by technology. This essay's goal is to investigate VBCs from the viewpoints of both businesses and consumers. In order to further our understanding of VBCs, the study synthesises the body of existing VBC literature and identifies areas of future focus for VBC research. We are given a conceptual framework that broadens our comprehension of VBCs and customer involvement. There are three hypothesised antecedents of consumer-VBC involvement: brand-related, social, and functional, coupled with the designation of four crucial elements of VBC (finance, governance, internet use, and brand orientation). The primary characteristics of VBCs and the various but connected viewpoints of the organisations and customers involved are examined for the first time in this study.